2018
DOI: 10.1158/1538-7445.sabcs17-p1-16-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-16-02: Phase II study of the feasibility and safety of radium-223 dichloride in combination with hormonal therapy and denosumab for the treatment of patients with hormone receptor-positive breast cancer with bone-dominant metastasis

Abstract: Background Radium-223 dichloride (Ra-223) is a therapeutic alpha particle-emitting radiopharmaceutical compound which have antitumor effect targeted on bone metastases. Alpha particles induces double strand DNA breaks and localized cytotoxic effect to cancer cells with limiting harm on normal tissues. We are conducting a phase II clinical trial of combination of Ra-223, hormonal therapy, and denosumab treatment in patients with hormone receptor (HR)-positive bone-dominant metastatic breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Association of Urology (EAU), NCCN, and many another guidelines, are unclear in defining the evaluation of response to any treatment of a non-measurable disease such as bone disease of the blastic type; for these reason numerous investigations have suggested the use of nuclear medicine techniques for patient selection and response evaluation, in addition similar to other therapies for mPC, a flare phenomenon with increase of bone metastases-related pain, or "increase" in apparent number of bone metastases on bone scan, may be noted during the first treatment cycles, and should not be interpreted as disease progression [14][15][16][17][18][19] The present study showed that besides that 223 In patients with both types of lung cancer, the 6 cycles were allowed to conclude; however, in one of them, the progression occurred 8 weeks after the end of the treatment. Taber AM, et al, showed that 5 patients with NSCLC who have received front-line chemotherapy, the progression free survival (PFS) at 6 months was 80.0% and 40.0% at 12 months in patients treated with 6 cycles of 223 Ra; in addition, only one patient developed SSE after 219 days, and the four remaining patients did not experience a SSE during follow-up [25] Tahara RK, et al, carried out a single-center phase II study to determine the efficacy and safety of neutropenia (23%), anemia (14%), and thrombocytopenia (18%) in median follow-up time was 4 months; in addition, there were no grade 3 or 4 AEs [26]; however, no PET/CT with any radiotracer was performed baseline or in the follow-up. Our results in two patients showed a good tolerability and no progression was observed in 18 F-NaF PET/CT.…”
Section: Nsclc (Figs 3 and 4)mentioning
confidence: 99%
“…Association of Urology (EAU), NCCN, and many another guidelines, are unclear in defining the evaluation of response to any treatment of a non-measurable disease such as bone disease of the blastic type; for these reason numerous investigations have suggested the use of nuclear medicine techniques for patient selection and response evaluation, in addition similar to other therapies for mPC, a flare phenomenon with increase of bone metastases-related pain, or "increase" in apparent number of bone metastases on bone scan, may be noted during the first treatment cycles, and should not be interpreted as disease progression [14][15][16][17][18][19] The present study showed that besides that 223 In patients with both types of lung cancer, the 6 cycles were allowed to conclude; however, in one of them, the progression occurred 8 weeks after the end of the treatment. Taber AM, et al, showed that 5 patients with NSCLC who have received front-line chemotherapy, the progression free survival (PFS) at 6 months was 80.0% and 40.0% at 12 months in patients treated with 6 cycles of 223 Ra; in addition, only one patient developed SSE after 219 days, and the four remaining patients did not experience a SSE during follow-up [25] Tahara RK, et al, carried out a single-center phase II study to determine the efficacy and safety of neutropenia (23%), anemia (14%), and thrombocytopenia (18%) in median follow-up time was 4 months; in addition, there were no grade 3 or 4 AEs [26]; however, no PET/CT with any radiotracer was performed baseline or in the follow-up. Our results in two patients showed a good tolerability and no progression was observed in 18 F-NaF PET/CT.…”
Section: Nsclc (Figs 3 and 4)mentioning
confidence: 99%